Gallo-Roman Bronzes and the Process of Romanization: The Cobannus Hoard - Pollini, John (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This book constitutes the first comprehensive publication of a cache of eight bronzes from east-central Gaul. The types of objects and accompanying inscriptions suggest that these bronzes originally came from a sanctuary of a god named Cobannus. The first part of the book describes, analyzes, and interprets the individual objects, which are divided between the J. Paul Getty Museum and the Shelby White - Leon Levy Collection. The latter part of this work places the cache within a chronological, cultic, and cultural context. The Cobannus hoard is valuable not only from an artistic point of view but also for the information it provides on many different aspects of the religious, social, and political life of Roman Gaul. The book is lavishly illustrated, with 2 maps and 117 illustrations.